Is the state really a Leviathan? Testing the model of Buchanan and Brennan in Europe - Możdżeń, Michał (Managerial Economics, 2014)
This article is an attempt to synthetically present and test the main conclusions of the State- as-Leviathan model. In the first part, the main assumptions of the model are described. In the second, the model is developed further in order to present main research hypotheses. In the third part, the critique and remarks on the model are reviewed. The fourth part is devoted to developing an empirical model and presenting the main findings of the analysis. The summary concludes the text with some suggestions for future research. The conducted analysis allows us to draw conclusions pointing to the less-than-perfect ability of the Leviathan model to describe real events in the areas of fiscal policy and taxation and, in some instances, seems to corroborate the conclusions ascribed to the "orthodox" theory of public finance criticized by Buchanan and Brennan. A regression model built upon a database on selected EU coun- tries derived from the Eurostat, European Commission and European Social Survey points to the fact that indeed the broadness of the taxable base can positively influence public revenue. And it also negatively affects the way people perceive the national government (in line with model assumptions). But when we turn to the influence of the broadness of the base on its perceived quality of life, we can find out that, in the countries with a relatively broad base, people's perceived life satisfaction is significantly higher (in line with "orthodox" theories). At the same time, the analysis corroborates to some extent Leviathan-model suggestions that progressive taxation is beneficial for the citizens in comparison to proportional, as some recent research shows.